The Three Giants of Bankruptcy Law in St. Louis - David A. Warfield (Washington University Journal of Law & Policy, 2017)
This Article reviews the significant roles three Washing University School of Law alumni had in shaping bankruptcy law—Jay L. Torrey, Walter D. Coles, and Barry Schermer. The Author notes Torrey’s contributions to the very first national permanent bankruptcy statute, Coles’s almost four decades of influence as a referee under the Bankruptcy Act of 1898, and Schermer’s contemporary contributions to bankruptcy law. The Article notes how these three individuals and their work span the almost 125 years of bankruptcy law across the country.
Keywords: Washington University; Washington University School of Law; Bankruptcy Code; Bankruptcy Law History; Torrey Bill; Federal Bankruptcy Law; St. Louis; Judge Schermer; Chapter 11 Bankruptcy; Chapter 7 Bankruptcy; Bankruptcy Appellate Panel